2021
DOI: 10.1080/00288330.2021.1875490
|View full text |Cite
|
Sign up to set email alerts
|

Frontal dynamics and water mass variability on the Campbell Plateau

Abstract: The Campbell Plateau is a dominating bathymetric feature of New Zealand's subantarctic region, strongly influencing the dynamics of both the Subtropical Front (STF) to the north and the Subantarctic Front (SAF) to the south. We present a consistent survey across New Zealand's subantarctic of the relationships between front positions, bathymetry and water masses. The northwest side of the Campbell Plateau is comparatively warm due to a southward extension of the STF over the plateau. The SAF is steered south an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Subantarctic Mode Water and Antarctic Intermediate Water are present over the Campbell Plateau and Bounty Trough, respectively (Forcén-Vázquez et al, 2021). The steep slope of the Campbell Plateau directs the flow of the full depth SAF around its south-eastern flank (Chiswell et al, 2015;Forcén-Vázquez et al, 2021). Previous work also found a similar pattern of radiolarian distribution in the Southwest Pacific region using factor analysis to show links to water mass associations in this region (Cortese and Prebble, 2015).…”
Section: Sw Pacific Sectormentioning
confidence: 57%
“…Subantarctic Mode Water and Antarctic Intermediate Water are present over the Campbell Plateau and Bounty Trough, respectively (Forcén-Vázquez et al, 2021). The steep slope of the Campbell Plateau directs the flow of the full depth SAF around its south-eastern flank (Chiswell et al, 2015;Forcén-Vázquez et al, 2021). Previous work also found a similar pattern of radiolarian distribution in the Southwest Pacific region using factor analysis to show links to water mass associations in this region (Cortese and Prebble, 2015).…”
Section: Sw Pacific Sectormentioning
confidence: 57%
“…In the S-STF, Chloropicon sieburthii made a substantial contribution in addition to the more dominant Chloroparvula pacifica (Figure S10). Whether this regional preference was linked to the bathymetric and hydrographic characteristics of the plateau (Forcén-Vázquez et al 2021; Neil et al 2004), the natural iron fertilization hypothesized for the region (Banse and English 1997; Gutiérrez-Rodríguez et al 2020) or a combination of these and other aspects cannot be concluded from our study. Moreover, an ASV belonging to this genus was also found to contribute substantially to protistan communities in coastal waters of the California Current Ecosystem (Gutierrez-Rodriguez et al 2019), highlighting the need of further studies to better understand the ecological drivers beyond coastal-oceanic trophic gradients responsible for the water mass preferences of such phytoplankton groups and species.…”
Section: Discussionmentioning
confidence: 79%
“…The oceanic water mass that enters this Sub-Antarctic zone is the Sub-Antarctic water mass (SAAW), which is modified within the Strait of Magellan by mixing with continental freshwater (runoff from glaciers and rivers), forming MSAAW and is found from the surface to 150 m depth. The properties of the MSAAW were established based on reported information (Sarmiento et al, 2004;Sievers and Silva, 2008;Silva et al, 2009;Llanillo et al, 2012;Torres et al, 2014;Forceń-Vaźquez et al, 2021). The strong salinity and alkalinity relationship reported for the Patagonian archipelago interior sea (41-56°S: Torres et al, 2011a;Torres et al, 2020) makes it possible to calculate alkalinity of the MSAAW using the equation: A Tsal (mmol kg -1 ) = 66.4 × Salinity + 1.1, (R 2 = 0.93, n=81; Figure 2; Supplementary Table 1).…”
Section: Water Mass Distribution Analysismentioning
confidence: 99%